PARAMETERS OF THE TRANSIENT SIGNALS DETECTED IN THE DECAMETER SURVEY OF THE NORTHERN SKY - Kravtsov, I. P.; Zakharenko, V. V.; Vasylieva, I. Y.; Mykhailova, S. S.; Ulyanov, O. M.; Shevtsova, A. I.; Skoryk, A. O. (Одеські астрономічні публікації, 2016)
Decameter all-sky Survey has been running at UTR-2 radio telescope over the past few years, about 70% of observational data are processed. The Survey is aimed at searching for pulsars and transient sources. Present work shows results of processing aforementioned part of data in order to find transient sources. The processing allowed detecting more than 500 signals. Distributions of the signals’ parameters (dispersion measures, galactic latitudes, “signal-to-noise-ratios” etc.) are obtained, which give reason to consider the vast majority of these pulses the signals from cosmic sources.